Increasing productivity through acid treatment (Multidisciplinary Journal of Science and Technology, 2025)
This article provides information about the most common method of treating the bottom of the well, acid treatment. The well was exposed to various surfactants along with acids and their effect on erosion was determined. The dependence of erosion on temperature was also studied experimentally.